2017
DOI: 10.1007/s11306-017-1194-y
|View full text |Cite|
|
Sign up to set email alerts
|

Non-invasive urinary metabolomic profiling discriminates prostate cancer from benign prostatic hyperplasia

Abstract: IntroductionProstate cancer (PCa) is one of the most common malignancies in men worldwide. Serum prostate specific antigen (PSA) level has been extensively used as a biomarker to detect PCa. However, PSA is not cancer-specific and various non-malignant conditions, including benign prostatic hyperplasia (BPH), can cause a rise in PSA blood levels, thus leading to many false positive results.ObjectivesIn this study, we evaluated the potential of urinary metabolomic profiling for discriminating PCa from BPH.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 72 publications
2
39
0
1
Order By: Relevance
“…The serum pyrimidines pseudouridine, 5,6‐dihydrouridine, 2’‐O‐methyluridine and 5‐methyluridine were elevated in cases compared to their matched control subjects, and the overall pathway showed a strong association. Pseudouridine is a modified nucleoside generated from the degradation of transfer RNA (tRNA), and previous studies have demonstrated elevated levels of modified nucleosides, particularly pseudouridine, in the biological fluids of cancer patients when compared to cancer‐free controls . Dihydrouridine is one of the most common modifications of tRNA and has been related to cancer, cancer cell growth and survival .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum pyrimidines pseudouridine, 5,6‐dihydrouridine, 2’‐O‐methyluridine and 5‐methyluridine were elevated in cases compared to their matched control subjects, and the overall pathway showed a strong association. Pseudouridine is a modified nucleoside generated from the degradation of transfer RNA (tRNA), and previous studies have demonstrated elevated levels of modified nucleosides, particularly pseudouridine, in the biological fluids of cancer patients when compared to cancer‐free controls . Dihydrouridine is one of the most common modifications of tRNA and has been related to cancer, cancer cell growth and survival .…”
Section: Discussionmentioning
confidence: 99%
“…Pseudouridine is a modified nucleoside generated from the degradation of transfer RNA (tRNA), and previous studies have demonstrated elevated levels of modified nucleosides, particularly pseudouridine, in the biological fluids of cancer patients when compared to cancer-free controls. 27,28 Dihydrouridine is one of the most common modifications of tRNA and has been related to cancer, 29,30 cancer cell growth and survival. 30 Our data also showed that serum dihydroorotate was inversely associated with lethal prostate cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, hnRNPM is expected to become a biomarker for predicting the invasiveness of PCa to guide the selection of treatment schemes. At present, most of the studies on PCa biomarkers focus on the specific proteins that are differentially expressed in PCa tissue compared to normal prostate tissue or in different grade groups using the Gleason grading system . We not only studied the expression level of hnRNPM in ADENO and BPH tissues, but also compared its expression in NEPC and ADENO tissues.…”
Section: Discussionmentioning
confidence: 99%
“…To our surprise, no significant changes were detected in specific proteins that are differentially expressed in PCa tissue compared to normal prostate tissue or in different grade groups using the Gleason grading system. 65,68 We not only studied the expression level of hnRNPM in ADENO and BPH tissues, but also compared its expression in NEPC and ADENO tissues. The results suggested that hnRNPM may play a significant role in the occurrence and progression of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort, citrate was not a predictor for PCa, and the significant metabolites choline and leucine did not improve diagnosis compared with PSA measurements. However, Perez‐Rambla et al have recently demonstrated significant metabolic differences in urine samples from PCa patients and BPH, without prior prostate massage . The predictive value of this classification model was moderate and only significant after variable selection, and thus requires validation in independent cohorts.…”
Section: Cancer Detection and Diagnosismentioning
confidence: 97%